Comparative Neurobiology of Biogenic Amines in Animal Models in Deuterostomes - D’Aniello, Enrico; Paganos, Periklis; Anishchenko, Evgeniya; D’Aniello, Salvatore; Arnone, Maria Ina (Frontiers in Ecology and Evolution, 2020)
In this study, we review the current knowledge on the presence of biogenic amines and their potential role as neurotransmitters in the nervous system of three groups of invertebrate deuterostomes: tunicates, cephalochordates and echinoderms. In addition to a general overview of biogenic amines in each subphylum we point most of our attention on a few species, as the sea squirts Ciona intestinalis, Ciona robusta, Phallusia mammillata and Ciona savignyi (tunicates), the lancelet amphioxus Branchiostoma lanceolatum and Branchiostoma floridae (cephalochordates), and the sea urchin Strongylocentrotus purpuratus (echinoderms). The choice of these species lies in the fact that they are currently the most studied invertebrate deuterostomes in the research field of Evolutionary Developmental biology (EvoDevo). Providing a comparative picture of the expression and role of neurotransmitters in deuterostomes will contribute to understand the evolution of these neural signalling systems. Such an approach represents a new frontier of comparative neuroanatomy and neurobiology, and a prerequisite to uncover the homology of neuronal structures and circuits in deuterostomes with such a different body plan organization and complexity.